« On nous déclare la guerre, c’est clair » - Camille Noûs (La Nouvelle Revue du Travail)
A key figure in the historic industrial action that overwhelmed France in 1995, Bernard Thibault - railman and former general secretary of France’s CGT labour union – kindly agreed to answer questions raised during a research project looking at Pierre Bourdieu’s construction of a European social movement. In this interview, Thibault revisits the genesis of a three-week strike that was ultimately able to reverse certain decisions that the French government, led at the time by Alain Juppé, had made. Far from analysing this movement in corporatist terms, Thibault highlights fundamental dynamics that - between the pressures exerted by union members and the restructuring plans that the government was trying to implement – transformed a leading union’s operating principles and culminated in 1995’s massive strike. By so doing, Thibault reveals the extent to which social conflict is predicated on a long period of preparation and adjustment; the need to balance the interests of professional groups and union forces; and how these efforts can, depending on the circumstances, lead to a successful outcome.